Pemanfaatan Magnetic Biochar dari Cangkang Sawit Sebagai Adsorben untuk Menyisihkan COD, Total Suspended Solid, Minyak dan Lemak dalam Air Buangan Domestik - David Andrio; Muhammad Ramadhan Saputra; Lita Darmayanti (Postgraduate, University of Mataram, 2024)
Greywater is wastewater from domestic activities sourced from kitchens, bathrooms, and laundry water. Greywater discharged directly into the environment can cause a decrease in surface water quality due to its high organic content, nutrients, pathogenic bacteria, and detergents and surfactants. One method that can be used to remove organic and nutrient content is adsorption. The success of the adsorption process is determined by several factors, such as adsorbent type, dosage, contact time, and others. One adsorbent that has attracted the attention of many researchers in recent years is magnetic biochar. This study aims to remove chemical oxygen demand (COD), total suspended solids (TSS), oil, and grease from greywater with a magnetic biochar adsorbent made from palm shells. The study was conducted by varying the dose of 1.2–8.55 g/l and the contact time of 30–150 minutes. The results showed that increasing the dose and contact time can increase the removal efficiency of COD, TSS, oil, and grease. The best results were obtained at a dose of 8.55 g/l and a contact time of 150 minutes. The removal of COD, TSS, oil, and grease was 87.91%, 88.46%, and 99.96%, respectively.